Effect of thermal aging on microleakage of current flowable composite resins - Nihan Gönülol; Ertan Ertaş; Aycan Yılmaz; Soner Çankaya (Elsevier, 2015)
Background/purpose: To evaluate the microleakage of Class V cavities restored with a new self-adhering resin composite after thermal cycling. Materials and methods: Standardized box-shaped Class V cavities were prepared on the buccal and lingual sides of 75 intact human molars (n = 150). The teeth were randomly divided into five groups of 30 cavities each and restored as follows: GroupVF: Vertise Flow (Kerr Corporation, Orange, CA, USA); Group OVF: OptiBond (Kerr) + Vertise Flow; Group SM: Clearfil SE Bond (Kuraray Medical Inc., Okayama, Japan) + Majesty Flow (Kuraray Medical Inc.); Group TM: Clearfil Tri-S Bond (Kuraray Medical Inc.) + Majesty Flow (Kuraray Medical Inc.); and Group UOA: Uni-etch acid (Bisco Inc., Schaumburg, IL, USA) + One-Step Bond (Bisco Inc.) + Aeliteflo (Bisco Inc.). The restorations were finished with aluminum oxide discs (Sof-Lex, 3M ESPE). The restorations were divided into three subgroups (n = 10) and subjected to 1000, 5000, and 15,000 thermal cycles. The teeth were immersed in 0.5% basic fuchsin solution for 24 hours. The dye penetration was examined under a stereomicroscope and scored. The results were statistically analyzed by Kruskal-Wallis, Mann-Whitney U, and Wilcoxon tests. Results: The Mann-Whitney U test revealed that for cementum leakage scores of 1000 cycled groups, Groups VF, UOA, and OVF showed higher microleakage than Groups TM and SM and the difference was statistically significant (P < 0.05). When the composite groups were compared for 5000 and 15,000 thermal cycles, no significant differences were detected for both enamel and cementum microleakage scores (P > 0.05). Conclusion: The sealing ability of the new self-adhering flowable composite is detected as similar to the traditional flowables when subjected to long term thermal aging.